Terms of exchange: an interview with Ian Merkel: Entrevista com Ian Merkel - Sá, Luiz César de (2024)
Ian Merkel was welcomed for a series of activities at the Postgraduate Program in History at the University of Brasília in July 2023. They revolved around Terms of Exchange: Brazilian Intellectuals and French Social Sciences, published by the University of Chicago Press (2022) and translated in Brazil by Edusp (2023). The book deals with Franco-Brazilian intellectual relations, which materialized mainly at the University of São Paulo from the 1930s onwards. This story, told so many times, re-emerges in a new light by privileging the agency of Brazilian intellectuals in the consolidation of French social sciences.